Energy consumption and temperature performance of cold stores in food industries in Thailand - T. Nuangjamnong; N. Chaomuang; P. Ongkunaruk (My University, 2024)
Refrigeration is an important part of the food supply chain because low temperature environment helps to maintain the quality of perishable products, thus prolonging their shelf life. However, the refrigeration system requires a considerable amount of energy consumption. This fact contributes to an increased cost in electricity bills and a reduction of competitiveness in markets. The current status of the energy consumption performance of cold stores in food companies in Thailand is scarcely available. The company stakeholders usually have no tool to evaluate their cold stores and cannot implement energy-efficiency measures effectively. In this study, a simple model based on thermal loads was developed and used to estimate the energy consumption of seven cold stores. On-site investigations were also conducted to assess their temperature performance. The results showed that the energy consumption of all investigated cold stores appeared to be better than both international and national average practices. Conversely, most cold stores exhibited moderate temperature performance. A case study of one cold store was conducted to improve its energy performance. Energy savings of 20% can be achieved by either precooling product prior to storage or using new curtain strips.
Keywords: Cold chain; Consumption; Refrigeration and Air Conditioning Technologies